(untitled) (Acta Entomológica Chilena, 2022)
The results of the aplication of the feeding test on three chilean acridid species: Trimerotropis ochraceipennis, Tetrixocephalus sergioi and Schistocerca americana, are presented. The data are summarized in three Tables, which show the degree of the specie’s preferences for the plants found in their habitat. A brief account of the applied techniques is offered.